PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SEKOLAH DASAR - Riskyka, Riskyka; Syafitri, Anis (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This research is motivated by the low mathematical communication ability of students in expressing ideas and relating the knowledge students have to real situations. This study aims to determine the contextual learning model influences students' mathematical communication ability better than the direct learning model. This research is a quasi-experimental research. The population of this study were all fourth grade students at SDN 050660 Kwala Bingai, Stabat, which consisted of three parallel classes with a total of 89 students. The sampling system used was cluster random sampling with classes IVA and IVB classes being sampled. Class IVA as the control class consisted of 30 students and class IVB as the experimental class consisted of 27 students. Data analysis was performed by two-way analysis of variance (ANOVA). The results showed that the contextual learning model had a better effect on students' mathematical communication abilities compared to the learning model. This shows that the contextual learning model provides a good change in developing students' mathematical communication ability.